Is children's gender a factor in academic achievement in primary school? - Joca Zurc (University of Maribor Press, 2019)
The purpose of this study was to examine academic performance among girls and boys in the second educational cycle of primary school on a representative sample. Another aim was to find factors explaining any difference between genders. The survey sample consisted of 1783 children. We collected the data with a standardized SSRS questionnaire and analysed it with nonparametric statistics. The results showed higher academic achievement among girls at a statistically significant level, particularly in reading, overall behaviour and motivation. Development of social skills, absence of behavioural problems and developmental deficits appeared as the strongest predictors of academic achievement in primary school. At the beginning of schooling, more attention needs to be focus on reading skills among boys.